1985
DOI: 10.1111/j.1365-2265.1985.tb01068.x
|View full text |Cite
|
Sign up to set email alerts
|

End‐organ Responses to Thyroxine Therapy in Subclinical Hypothyroidism

Abstract: We studied variables known to change with thyroid hormone status in 18 patients with subclinical hypothyroidism before and during treatment with thyroxine in a dose sufficient to restore the plasma TSH response to TRH to normal. There was an associated increase in both plasma total T4 and free T4 within the normal range but plasma total T3 and free T3 were unchanged. As a result of thyroxine treatment there was a small but significant increase (P less than 0.05) in left ventricular ejection fraction (LVEF) wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
26
1
5

Year Published

1989
1989
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(38 citation statements)
references
References 32 publications
6
26
1
5
Order By: Relevance
“…These results are in accordance with those of the small number of published reports about the effect of L-T4 treatment on lipoprotein and apolipoprotein fractions in patients with subclinical hypothyroidism [25,26]. But other studies have failed to demonstrate significant changes in total cholesterol following L-T4 treatment [27,28]. These conflicting results may be explained by the difference in definition of subclinical hypothyroidism and/or the characteristics (sex, age, BMI) of patients and control groups.…”
Section: Discussionsupporting
confidence: 51%
“…These results are in accordance with those of the small number of published reports about the effect of L-T4 treatment on lipoprotein and apolipoprotein fractions in patients with subclinical hypothyroidism [25,26]. But other studies have failed to demonstrate significant changes in total cholesterol following L-T4 treatment [27,28]. These conflicting results may be explained by the difference in definition of subclinical hypothyroidism and/or the characteristics (sex, age, BMI) of patients and control groups.…”
Section: Discussionsupporting
confidence: 51%
“…It is probably due to thyroid autoimmunity, which is known to increase with age as reported in the Wickham survey. 13 Besides, prevalence was more in females and increased with age, which is similar to that observed by Parle et al 14 Prevalence was also more in postmenopausal women. But in this study TSH level showed a gradual decrease as the age advances whereas most of the TPOAb positive people are in the age group of 26-30 years of age.…”
Section: Discussionsupporting
confidence: 78%
“…The results include a wide range of cardiac abnormalities also by using radionuclide ventriculography. Foldes et al (36) found a lower LV ejection fraction in SH than in euthyroid controls, both at rest and during physical exercise, whereas Bell et al (37) reported an LV ejection fraction decrease only during maximal exercise. These discrepancies might be in part related to the different selection (age, sex distribution, and inclusion of patients with previous hyperthyroidism or unstable SH), to the different diagnostic criteria (too wide range of TSH levels) and to the impossibility of defining the onset and length of thyroid failure in the majority of assessed populations.…”
Section: Discussionmentioning
confidence: 99%